Stress dynamics between clinical supervisors and allied health students: a scoping review protocol - Yongsheng Wang; XinRong Li; Piao Wang; Laurie Peebles; Aine O'Connor (BMJ Open)
Introduction The aim of this scoping review is to connect theoretical research related to stress with practical applications to supervision experiences within allied health professions. Understanding the implications of stress between clinical supervisors and allied health students will allow for better insights to improve supervisory methods within clinical training, stronger mentorship and lead to better quality patient care.Methods and analysis This review is conducted according to Joanna Briggs Institute (JBI) methodology for scoping reviews, which includes defining the research question, developing inclusion criteria and searching for, selecting, extracting and analysing the evidence. A literature search will be conducted in MEDLINE (PubMed), CINAHL (EBSCO), ERIC (EBSCO), PsycINFO (EBSCO) and Embase (Elsevier), as well as various grey literature resources. Studies will be included if they focus on undergraduate or graduate allied health students in a clinical setting and allied health clinical educators, and report on outcomes related to stress dynamics between these two populations. Results will pass through title/abstract and full-text screening before data are extracted using a tool developed by the reviewers. Data will be analysed and summarised descriptively and presented in both tabular and narrative formats.Ethics and dissemination Ethical approval is not required for this scoping review. Results will be disseminated in peer-reviewed publications and professional conferences.Trial registration number The protocol was registered with Open Science Framework on 2 October 2024 (https://doi.org/10.17605/OSF.IO/REK7Z).